2010
DOI: 10.1007/s00394-010-0129-4
|View full text |Cite
|
Sign up to set email alerts
|

Breast milk tocopherol content during the first six months in exclusively breastfeeding Greek women

Abstract: This study is among few in literature to determine tocopherol content of breast milk in European women and detect dietary factors that may influence its values. The only maternal dietary characteristic to affect breast milk tocopherol content was mothers' total fat intake, while tocopherol intake seems to have no effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 39 publications
7
52
4
2
Order By: Relevance
“…Jansson et al, 1981). A very similar value in three-month-old infants was reported in one recent study (3.5 mg α-tocopherol per litre (0.54 mg/100 kcal) (Antonakou et al, 2011), whereas different values have been reported in other studies, .e.g. 2.3 mg α-tocopherol per litre (0.36 mg/100 kcal) (Tijerina-Saenz et al, 2009).…”
Section: Vitamin E Content Of Human Milksupporting
confidence: 56%
“…Jansson et al, 1981). A very similar value in three-month-old infants was reported in one recent study (3.5 mg α-tocopherol per litre (0.54 mg/100 kcal) (Antonakou et al, 2011), whereas different values have been reported in other studies, .e.g. 2.3 mg α-tocopherol per litre (0.36 mg/100 kcal) (Tijerina-Saenz et al, 2009).…”
Section: Vitamin E Content Of Human Milksupporting
confidence: 56%
“…This value was closely corroborated in three-month-old infants in one recent study (3.48 mg/L) (Antonakou et al, 2011) Taking the AI of IoM (2000b) and NHMRC (2006) as a basis, the Panel considers that an alphatocopherol intake of 5 mg per day is adequate for the majority of infants aged from 6 to < 12 months. This covers also infants with the highest observed PUFA intakes (i.e.…”
Section: To < 6 Monthsmentioning
confidence: 58%
“…The other five studies (Schweigert et al, 2004;Quiles et al, 2006;Romeu-Nadal et al, 2006;SziklaiLaszlo et al, 2009;Antonakou et al, 2011) were conducted in mothers of full-term infants in the EU. In these studies, mean α-tocopherol concentration in human milk, measured by high-performance liquid chromatography (HPLC), ranged from about 3 mg/L to about 25 mg/L (including all stages of lactation).…”
Section: Breast Milkmentioning
confidence: 99%
“…α-Tocopherol content in human milk of about 3.5 mg/L has been noted (EFSA NDA Panel, 2013), based on Antonakou et al (2011). A comprehensive search of the literature published after January 2000 was performed as preparatory work to the present Opinion in order to identify data on breast milk α-tocopherol concentration (LASER Analytica, 2014).…”
Section: Breast Milkmentioning
confidence: 99%